Genetic variability, traits interactions, and principal component analysis of broad-leaf mustard group (Brassica juncea L.) to focus on the yield improvement - Md Mahmudul Hasan Khan; BC Kundu; Suprio Ghosh; Gazi Nazmul Hasan; Md Rashidul Hasan Anik; Md Mainul Islam; Mst Shamima Yesmin; Nasira Akter; Krisna Chandra Saha; Md Torikul Islam (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Mustard (Brassica spp.), one of the most important oilseed crops, is currently the third-largest source of vegetable oil in the world. In Rabi, 2022-2023 at the Regional Agricultural Research Station (RARS), Barishal, research of Brassica juncea L. was carried out with 10 genotypes to assess yield and yield contributing features. The RCBD design for the experiment included three replications. Plant height, the number of primary branches, the number of secondary branches, and the number of seeds per siliqua were the characteristics for which the analysis of variance findings indicated that there were very significant differences. Using the UPGMA cluster analysis, four distinct clusters were found among the analyzed accessions. Cluster II obtained the most accessions (7), averaging 1765.28 kgha-1, representing 25.20% of the average group mean yield. A correlation study focuses on the highly significant and positive correlation between a crop's associated features and its yield. The overall amount of variance was found to be 46.18% for PC1 and 17.61% for PC2 using Principal Component Analysis (PCA). Maturity duration ranged from 106-110 days while the 50% flowering period varied from 43-46 days. Seed yield ranged from 1463 to 1970 kgha-1 and BJ-11536(12)-1 produced the highest yield among the genotypes. Which was it produced 23.58% and 20.41% higher yields than check varieties BARI Sarisha-11 and BARI Sarisha-19, respectively. The second highest yield was recorded from BJDH-05 which produced 18.90% and 15.85% higher yield over the check varieties BARI Sarisha-11 and BARI Sarisha-19, respectively. The lowest seed yield (1463 kgha-1) was obtained from the entry BJ-53611(12)-8. Based on, statistical analysis considering seed yield and other yield contributing characters, four lines BJ-11536(12)-1, BJDH-05, BJDH-20, BJ-11536(12)-5, and BJ-1110(12)-1 were noted as high-yielding accessions and could be used for future breeding program.